Effective photoconductivity of exfoliated black phosphorus for optoelectronic switching under 1.55 μm optical excitation - Penillard, A. (2016)
We present a microwave photoconductive switch based on exfoliated black phosphorus and strongly responding to a 1.55 μm optical excitation. According to its number of atomic layers, exfoliated black phosphorus presents unique properties for optoelectronic applications, like a tunable direct bandgap from 0.3 eV to 2 eV, strong mobilities, and strong conductivities. The switch shows a maximum ON/OFF ratio of 17 dB at 1 GHz, and 2.2 dB at 20 GHz under 1.55-μm laser excitation at 50 mW, never achieved with bidimensional materials.